Development of a Web-Based E-Survey Application for Assessing Good Corporate Governance Understanding at PT. XYZ - Cristian Richardo Anin; Nia Ambarsari; Sinung Suakanto (Digital Zone: Jurnal Teknologi Informasi dan Komunikasi, 2023)
PT. XYZ is currently facing challenges in conducting their Good Corporate Governance (GCG) comprehension survey due to the manual distribution and collection of survey data using Google Drive and Microsoft Excel. To address this issue, the researcher proposes the development of a web-based E-Survey application to streamline the survey process. The development follows the waterfall model and utilizes the Laravel framework. To ensure its effectiveness, the application undergoes Load Testing to assess its performance with multiple users and User Acceptance Test (UAT) to evaluate its alignment with company requirements. The results indicate that the system operates optimally with up to 100 users and receives a favorable score on the System Usability Scale (SUS). This application provides a suitable solution for conducting comprehension surveys at PT. XYZ.